Using Real-Time Spatial Delphi to locate Loading bays and Parcel Lockers - ICASP14; Pilla, Francesco; Giuffrida, Nadia; Calleo, Yuri (My University, 2023)
Urban logistics has become part of the citizensﾒ life, who often use e-commerce options to buy goods and groceries. The constant increase of this phenomenon which has been witnessed in recent years led to a consequent increase in the externalities associated with it, such as air pollution, traffic, land occupation and accidents generated by the vehicles carrying out the delivery of parcels in our cities. The decision on their correct location should respect high-quality technical standards but cannot disregard the objectives pursued by the different actors involved in the decision-making process related to logistics. Experts are called to identify common problems and answer different questions, where obtaining a univocal consensus may require much effort, due to their different ideas and visions. This paper proposes a participatory approach to identify suitable locations for automated parcel lockers and smart loading bays, involving the main actors in the decision-making process. The case study is the city of Dublin (Ireland), where an Urban Living Lab of the H2020 project SENATOR (Smart Network Operator Platform enabling Shared, Integrated and more Sustainable Urban Freight Logistics) is based. To overcome this challenge, we combine a multi-criteria analysis, involving a panel of experts partners of the project with a high expertise degree to identify suitable locations, and a revised Real-Time Spatial Delphi technique, useful to obtain a spatial convergence of opinion in a short time, enhancing the overall process.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED